2018
DOI: 10.2174/1389202919666180101154916
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Factors Involved in Spinal Muscular Atrophy Pathways as Possible Disease-modifying Candidates

Abstract: Spinal Muscular Atrophy (SMA) is a neuromuscular disorder caused by mutations in the SMN1 gene. Being a monogenic disease, it is characterized by high clinical heterogeneity. Variations in penetrance and severity of symptoms, as well as clinical discrepancies between affected family members can result from modifier genes influence on disease manifestation. SMN2 gene copy number is known to be the main phenotype modifier and there is growing evidence of additional factors contributing to SMA severity. Potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 203 publications
0
23
0
Order By: Relevance
“…SMN protein reduction causes cellular changes which directly or indirectly provoke the deregulation of several processes involved in cell homeostasis, including autophagy and apoptosis 31 . Nonetheless, intracellular pathways related to neurotrophic communication or calcium regulation may be impaired in SMA pathology and contribute to modifying the evolution of the disease 32 . In this context, we have previously demonstrated that treating SMA mice with the calpain inhibitor calpeptin had a positive effect on survival and motor function 21 .…”
Section: Discussionmentioning
confidence: 99%
“…SMN protein reduction causes cellular changes which directly or indirectly provoke the deregulation of several processes involved in cell homeostasis, including autophagy and apoptosis 31 . Nonetheless, intracellular pathways related to neurotrophic communication or calcium regulation may be impaired in SMA pathology and contribute to modifying the evolution of the disease 32 . In this context, we have previously demonstrated that treating SMA mice with the calpain inhibitor calpeptin had a positive effect on survival and motor function 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Spinal Muscular Atrophy (SMA) is a monogenic neuromuscular syndrome triggered due to mutations in Survival of motor neurone 1 (SMN1) gene (Maretina et al, 2018). The SMA patients maintain in situ copy of the paralog SMN2 gene, which produces reduced amounts of the SMN protein.…”
Section: Effects Of Hdaci In Various Neurodegenerative Disorders Modementioning
confidence: 99%
“…We believe that in terms of its impact on SMA phenotype, SMN2 copy number might be considered as the tip of an iceberg of which other genetic and epigenetic features, most notably SNVs, represent the submerged part with relevant effects to phenotype of the patients with SMA (figure). A number of other genes have been proposed as candidate modifiers of the SMA phenotype including methylation status of SMN2 (reviewed in Maretina et al, 2018), 39 although none of them are yet validated in clinical practice. Given that SMN2 variants modify the disease phenotype and that transcripts derived from SMN2 are targets for splicing modifiers in the therapeutic scenario, it is essential to gain a thorough insight into the complete SMN2 sequences of discordant patients.…”
Section: Yesmentioning
confidence: 99%